TESTING THE UNBIASED EXPECTATIONS HYPOTHESIS - Sabyrzhanov, Damir; Mussin, Maxat (Nazarbayev University Graduate School of Business, 2023)
The complex relationship between exchange rates and interest rates has long attracted the interest of academic researchers and practitioners in the financial world, generating extensive research and practical discussions. This multifaceted interaction is of utmost importance, affecting a wide range of individuals and organizations, from individual investors trying to navigate turbulent forex markets, to policymakers carefully crafting monetary policy, to global economists trying to decipher macroeconomic trends. The focus of this discussion is the unbiased expectations hypothesis (UEH), an influential theory that posits a direct correlation between expected exchange rate movements and the different interest rates observed in different countries..
Keywords: Type of access: Open